Rising prevalence of human papillomavirus–related oropharyngeal cancer in Australia over the last 2 decades. Issue 5 (25th June 2015) - Hong, Angela; Lee, C. Soon; Jones, Deanna; Veillard, Anne‐Sophie; Zhang, Mei; Zhang, Xiaoying; Smee, Robert; Corry, June; Porceddu, Sandro; Milross, Christopher; Elliott, Michael; Clark, Jonathan; et al.
Abstract: Background: This study provides Australian data on the characteristics of human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (SCC) over the last 2 decades. Methods: The HPV status of 515 patients with oropharyngeal SCC diagnosed between 1987 and 2010 was determined by HPV E6‐targeted multiplex real time polymerase chain reaction assay (PCR) and p16 immunohistochemistry. Results: The HPV positivity rate increased from 20.2% (1987–1995) to 63.5% (2006–2010). Among HPV‐positive oropharyngeal SCC over the study period, the median age increased from 55.4 years to 59.8 years ( p = .004) and there was a trend of an increasing proportion of never smokers (19.2% to 34.0%). The use of radiation therapy (RT) in patients with HPV‐positive oropharyngeal cancer increased from 26.9% to 68.1% ( p = .007) and we also observed a trend of improved outcomes. Conclusion: Our data show a rising prevalence of HPV‐positive oropharyngeal SCC in Australia over the last 2 decades. These patients with HPV‐positive oropharyngeal SCC are now presenting at an older age and about one third have never smoked. © 2015 Wiley Periodicals, Inc. Head Neck 38: 743–750, 2016